Filamin A in platelets: Bridging the (signaling) gap between the plasma membrane and the actin cytoskeleton - De Silva, Enoli; Hong, Felix; Falet, Hervé; Kim, Hugh (Frontiers in Molecular Biosciences, 2022)
Platelets are anucleate cells that are essential for hemostasis and wound healing. Upon activation of the cell surface receptors by their corresponding extracellular ligands, platelets undergo rapid shape change driven by the actin cytoskeleton; this shape change reaction is modulated by a diverse array of actin-binding proteins. One actin-binding protein, filamin A (FLNA), cross-links and stabilizes subcortical actin filaments thus providing stability to the cell membrane. In addition, FLNA binds the intracellular portion of multiple cell surface receptors and acts as a critical intracellular signaling scaffold that integrates signals between the platelet’s plasma membrane and the actin cytoskeleton. This mini-review summarizes how FLNA transduces critical cell signals to the platelet cytoskeleton.